The impact of maintenance on peri-implant health - Rosing, C. K.; Fiorini, T.; Haas, A. N.; Muniz, Fwmg; Oppermann, R. V.; Susin, C. (Braz Oral Res, 2019)
Most of the literature evaluating dental implants focuses on implant survival, which is a limited proxy for the successful rehabilitation of patients with missing teeth. Success should include not only survival but also lack of mechanical, biological, and esthetics problems. A comprehensive review of local and systemic risk factors prior to implant placement will allow the tailoring of treatment planning and maintenance protocols to the patient's profile in order to achieve longitudinal success of the therapy. This review discusses the role of controlling different risk factors and prevention/treatment of peri-implant mucositis in order to avoid peri-implantitis. Although the literature addressing the topic is still scarce, the existing evidence shows that performing optimal plaque control and regular visits to the dentist seem to be adequate to prevent peri-implant lesions. Due to impossibility of defining a probing depth associate with peri-implant health, radiographic evaluations may be considered in the daily practice. So far, there is a strong evidence linking a past history of periodontal disease to peri-implant lesions, but this is not so evident for other factors including smoking and diabetes. The prevention of biological complications starts even before implant placement and include a broader analysis of the patient risk profile and tailoring the rehabilitation and maintenance protocols accordingly. It should be highlighted that the installation of implants does not modify the patient profile, since it does not modify genetics, microbiology or behavioral habits of any individual.
Rosing, Cassiano KuchenbeckerFiorini, TiagoHaas, Alex NogueiraMuniz, Franciso Wilker Mustafa GomesOppermann, Rui VicenteSusin, CristianoengReviewBrazilBraz Oral Res. 2019 Sep 30;33(suppl 1):e074. doi: 10.1590/1807-3107bor-2019.vol33.0074. eCollection 2019.
Keywords: *Bone-Implant Interface/diagnostic imaging; Dental Implants/*adverse effects; Dental Plaque/prevention & control; Humans; Oral Hygiene; Peri-Implantitis/etiology/*prevention & control; Periodontal Index; Periodontitis/etiology/*prevention & control; Radiography, Dental; Risk Factors; Stomatitis/etiology/*prevention & control